Dari Sunat Fisik ke Sunat Hati: Evolusi Makna Sunat dalam Iman Kristen - Royke Lontoh (Sekolah Tinggi Teologi Bethel Ambon, 2025)
This study examines the evolution of the meaning of circumcision in Christian faith from a physical covenantal sign in the Old Testament to the concept of “circumcision of the heart” in the New Testament. Using a qualitative-descriptive approach based on library research, this article analyzes biblical texts and theological perspectives concerning circumcision within the continuity of God’s covenant. The findings indicate that physical circumcision in the Old Testament functioned as a sign of God’s covenant with Israel, symbolizing identity, holiness, and obedience to the Law. However, the New Testament reinterprets circumcision as an inward spiritual transformation accomplished through faith in Christ and the work of the Holy Spirit. The Apostle Paul emphasizes that true circumcision is not merely external ritual practice but the renewal of the heart that produces a new life in Christ. Therefore, physical circumcision is no longer a requirement for salvation for non-Jewish Christians. This study concludes that the essence of Christian identity lies in spiritual transformation, obedience, and holiness manifested through the “circumcision of the heart.”